Differentiated Learning Through Problem Based Learning Model to Improve Students' Critical Thinking Skills on Heat and Its Transfer - Lianti, Mexi; Stepanus Sahala Sitompul; Syaiful B Arsyid (Jurnal Penelitian Pembelajaran Fisika, 2025)
This study aims to determine the profile of skills and improvement of critical thinking of students before and after implementing differentiated learning through the Problem Based Learning model on the material of heat and its transfer. The method used is a Pre-Experimental Design with a One Group Pretest-Posttest Design. The research sample consists of one class with 31 students. The research data were obtained by providing a critical thinking skills test in the form of pretest and posttest questions consisting of 5 essay questions. The results show that the average score for the pretest is 47.90% (medium category) and the posttest is 69.03% (high category). Based on calculations using paired sample tests, a sig (2-tailed) value of 0.00 < 0.05 indicates a significant improvement in posttest scores after treatment with differentiated learning through the Problem Based Learning model. Therefore, it can be concluded that differentiated learning with the Problem Based Learning model can enhance students' critical thinking skills on the topic of heat and its transfer.